Antigenic analysis of outer membrane protein of Vibrio species and development of versatile recombinant vhDnaJ vaccine against vibriosis - Mursidi, Fathin Amirah (2018)
Vibriosis is one of the most catastrophic bacterial disease caused by infection of Vibrio spp. which frequently attacks marine cultures in all life stages. Recently, vibriosis was reported to cause vast mortality of tiger grouper cultured in deep sea cages in Langkawi, Malaysia. This disease frequently occurs during dry months when the water temperature is elevated. Although vibriosis is controlled through vaccination, the existence of different strains and antigenic diversities of Vibrio species and their serotypes have led to slow progress of vaccine development. Therefore, the development of a versatile vaccine that can fight against multiple Vibrio by eliciting protection against homologous and heterologous strains is urgently needed both for hindering vibriosis infections and to avoid the exploitation of antibiotics in aquaculture industry. Hence, the aim of this research was to search for the most antigenic OMPs protein among Vibrio sp. by analysing the protein’s ability to elicit homologous and cross antigenicities and to develop a potentially versatile recombinant Vibrio vaccine. The safety of the developed vaccine was also assessed in gnotobiotic Artemia species. OMPs of Vibrio harveyi strain VH1, V. alginolyticus strain VA2, V. parahemolyticus strain VPK1 and Photobacterium damselae strain PDS1 isolated from diseased groupers were extracted and characterized by SDS-PAGE and detection of immunogenic proteins were done by Western immunoblotting. The polyclonal antiserum of V. harveyi strain VH1 raised from rabbit induced strong antigenic responses on homologous OMPs antigens of V. harveyi strain VH1 and cross reacted against heterologous OMPs antigens of V. parahemolyticus strain VPK1, V. alginolyticus strain VA2 and P. damselae strain PDS1 at molecular weight of 32 kDa. Therefore, further studies were conducted on the antigenically heterologous 32 kDa OMP of V. harveyi strain VH1 as a potential vaccine candidate. The 32 kDa protein band was a molecular chaperone DnaJ, designated as vhDnaJ after submitted for N-terminal amino acid sequencing analysis. The vhDnaJ gene was amplified and cloned in pET-32 Ek/LIC vector and expressed in host BL21 (DE3) Escherichia coli. Bioinformatics analysis indicated that the target gene was highly conserved among Vibrio sp. and highly antigenic by comprising 40 antigenic sites. Successful recombinant vhDnaJ protein expression expressed under 30°C for 10 hour was detected at 49 kDa band by SDS-PAGE and Western immunoblotting by using Anti-HisTag monoclonal antibodies. The bioencapsulation of the inactivated recombinant vhDnaJ cells vaccine into Artemia sp. demonstrated that the species could survive up to ±83.3% after 36 h postencapsulation, signifying the vaccine was safe and might be beneficial to the host. In conclusion, the cumulative evidences of the 32 kDa OMP of V. harveyi strain VH1 by being the most antigenic against homologous and heterologous isolates and highly conserved among the tested Vibrio strains in in-vitro antigenicity and bioinformatics study could be a promising versatile vaccine antigen against multiple Vibrio sp. in grouper culture. Moreover, the successful expression of the protein of interest and verified safety of the developed recombinant vhDnaJ vaccine in Artemia sp. open the way for future preparation of crude recombinant vaccine as well as to assess its efficacy in marine fish.